2021
DOI: 10.3390/su13179752
|View full text |Cite
|
Sign up to set email alerts
|

How to Restrain Regulatory Capture and Promote Green Innovation in China. An Analysis Based on Evolutionary Game Theory

Abstract: In response to severe environmental challenges, green innovation (GI) has been thoroughly considered by various governments. Although China has promulgated many environmental policies to promote environmental governance, regulatory capture and the lack of independent external supervisors lead to a challenging future. This study employs an evolutionary game method to explore how the policy burden and media affect decision-making between local governments and manufacturing enterprises. On this basis, the simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In terms of the causes of regulatory capture, Yuan concluded that policy burden is the main factor leading to regulatory capture. When the policy burden exceeds a certain threshold, it results in regulatory capture and hinders green innovation (10). In terms of the consequences of regulatory capture, Xu et al concluded that regulatory capture negatively regulates the promoting effect of environmental regulation on R&D and innovation (41).…”
Section: Regulatory Capturementioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the causes of regulatory capture, Yuan concluded that policy burden is the main factor leading to regulatory capture. When the policy burden exceeds a certain threshold, it results in regulatory capture and hinders green innovation (10). In terms of the consequences of regulatory capture, Xu et al concluded that regulatory capture negatively regulates the promoting effect of environmental regulation on R&D and innovation (41).…”
Section: Regulatory Capturementioning
confidence: 99%
“…In terms of the environmental behavior of enterprises, few scholars quantitatively study the effect of the combination of incentive-based and constraint policies. In addition, the environmental behavior of local governments mainly involves economic preferences (8), reward and punishment mechanisms (88), policy burdens (10), and environmental protection tax policies (6,42), and few scholars have considered both the economic and environmental preferences of local governments. (2) In terms of the relevant subjects involved in environmental pollution governance, existing studies mainly include the central government (67), local governments (84), polluting enterprises (85), third-party environmental protection organizations (87), the public (86), and the media (79), and few scholars include enterprises, local governments, the central government, and the media in the same model to study environmental pollution governance.…”
Section: Study On the Applicability Of Game Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of the participants in environmental governance, Bian et al (2022) explored the regulatory effect of the combination of formal and informal environmental regulation with public participation under heterogeneous government regulations, which can further promote green behavior by enterprises. Yuan (2021) analyzes the influence of the policy burden and the media on decision-making between local governments and manufacturing enterprises, and demonstrated that the supervisory role of the media can inhibit the regulatory capture caused by the policy burden to a certain extent, so as to promote the green technology innovation by enterprises. Chu et al (2022) established a tripartite evolutionary game model involving the local government, polluting enterprises and the public, and suggested that public supervision could help reduce the regulatory burden on local government and that the public could cooperate with relevant government policies to improve the effectiveness of environmental supervision.…”
Section: Related Literaturementioning
confidence: 99%
“…According to this view, environmental regulation essentially impacts the private costs of enterprises, is not conducive to the improvement of enterprises' independent innovation ability and has a restraining effect on economic growth and environmental efficiency. Kneller and Manderson [71] and Yuan [72] found that environmental regulation has an inhibiting effect on enterprises' technological innovation. In addition to environmental regulations, external environment can also affect the green innovation of enterprises through public anger and condemnation, for example, in response to nearby environmental spills, firms may increase both environmental innovation input and output [73].…”
Section: External Driving Factors Of Green Innovationmentioning
confidence: 99%